Endovascular Approach for Management of Bullet Embolization to the Heart. (May 2018) - Mojtahedi, Alireza; Contractor, Sohail; Kisza, Piotr S.
Bullet embolization to the right heart through the vasculature is seen infrequently in cases presenting with penetrating trauma. Patients with unstable hemodynamic status are managed operatively. For a patient with stable hemodynamic parameters, diagnostic evaluation such as computed tomography angiogram, echocardiogram, or angiography could be performed to select the best treatment option. Endovascular treatment is employed infrequently in these cases but can be a viable option for select patients. We present a case of a bullet embolus to the right ventricle treated successfully with endovascular approach and discuss the technical aspects of this approach.